2007
DOI: 10.4049/jimmunol.179.10.6604
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mimics Can Induce Novel Self Peptide-Reactive CD4+ T Cell Clonotypes in Autoimmune Disease

Abstract: It has been postulated that infectious agents may precipitate autoimmune disease when T cell responses raised against the pathogen cross-react with self-peptides, a phenomenon known as molecular mimicry. However, there are very little data available characterizing the similarity between the repertoire of the cross-reactive self-specific T cell population compared with the pathogen-specific T cell repertoire. In this study, we use immunoscope analysis to identify the T cell populations induced upon priming SJL/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
6
0
2
Order By: Relevance
“…Exposure to different gut microbiota products, including short-chain fatty acid and polysaccharide A, may differentiate MOG-reactive CD4 + T cells into an autoreactive phenotype through molecular mimicry (89). It is also plausible that the induction of autoimmunity in the TNFR2 2/2 2D2 mice relies on a direct effect of gut microbiota on B cell function.…”
Section: Gut Microbiota In Tnfr2mentioning
confidence: 99%
“…Exposure to different gut microbiota products, including short-chain fatty acid and polysaccharide A, may differentiate MOG-reactive CD4 + T cells into an autoreactive phenotype through molecular mimicry (89). It is also plausible that the induction of autoimmunity in the TNFR2 2/2 2D2 mice relies on a direct effect of gut microbiota on B cell function.…”
Section: Gut Microbiota In Tnfr2mentioning
confidence: 99%
“…One of the facets of polyspecificity in the context of autoimmune diseases is molecular mimicry, defined as sequence similarities between foreign and self-antigens that result in the cross-activation of autoreactive T and B cells by microbial Ags (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). Originally, an important degree of sequence homology was considered necessary to explain molecular mimicry, but subsequent extensive dissection with synthetic peptide combinatorial libraries revealed that TCR Ag recognition is quite degenerate, and Ag similarity, resulting in the productive triggering of a given TCR, goes beyond sequence homology (10,38,39).…”
mentioning
confidence: 99%
“…Une fois le processus activé, la réponse auto-immunitaire devient indépendante d'une exposition continue au facteur dé-clenchant environnemental et, de ce fait, le processus se perpétue de lui-même et est irréversible. Une réactivité croisée spécifique d'épitopes entre des micro-organismes et des tissus du soi a été démontrée dans certains modèles animaux [59] . Réciproquement, dans la plupart des maladies auto-immunes humaines, l'imitation moléculaire semble être un facteur de la progression d'une réponse auto-immune infraclinique préexistante et non un facteur de l'initiation d'une auto-immunité par rupture de la tolérance [60] .…”
Section: Agents Pathogènes Intestinauxunclassified